A blind expert test of contrarian claims about climate data. (July 2016) - Lewandowsky, Stephan; Ballard, Timothy; Oberauer, Klaus; Benestad, Rasmus
Abstract : Highlights: We identified representative claims about data made by climate contrarians. Experts evaluated these claims translated into an economic context for accuracy and credibility. The contrarian claims were found to be misleading in this blind test. Mainstream scientific interpretations of the same data were found to be accurate in the blind test. Abstract: Although virtually all experts agree that CO2 emissions are causing anthropogenic global warming, public discourse is replete with contrarian claims that either deny that global warming is happening or dispute a human influence. Although the rejection of climate science is known to be driven by ideological, psychological, and political factors rather than scientific disagreement, contrarian views have considerable prominence in the media. A better understanding of contrarian discourse is therefore called for. We report a blind expert test of contrarian claims about climatological variables. Expert economists and statisticians were presented with representative contrarian statements (e.g., "Arctic ice is recovering") translated into an economic or demographic context. In that blind test, contrarian claims were found to be misleading. By contrast, mainstream scientific interpretations of the data were judged to be accurate and policy relevant. The results imply that media inclusion of contrarian statements may increase bias rather than balance.